The Distinctiveness Problem of Analogical Arguments - Liao, Yanlin (Informal Logic, 2024)
The orthodox view holds that analogical arguments are a distinctive type of argument, while the eliminative view and its enhanced variant proposed in this paper contend that analogical arguments can be reducible to non-analogical arguments by eliminating the similarities proposition. This paper shows that the existing defense for the orthodox view fails to tackle the challenge posed by the eliminative view and its enhanced variant. The new defense for the distinctiveness of analogical arguments argues that an analogical argument is composed of both a conductive and principle-based argument. Consequently, analogical arguments remain irreducible, as the similarities proposition is not eliminated.